Sense and intention: reading science fiction worlds and characters - Ismail @ Hamdan, Shahizah; Omar, Noritah (Penerbit Universiti Kebangsaan Malaysia, 2010)
This paper examines prototype worlds and characters in selected Science Fiction (SF) texts. It utilises certain principles of I.A Richard’s Practical Criticism, particularly in relation to “sense” and “intention”, as the analytical framework. It is found that the analysis of the worlds and characters reveals the authors’ intention i.e. his aim, conscious or unconscious, and the effect that is promoted to the readers. The words used by the authors to describe the SF worlds and characters have a task to perform and that is to convey meaning to readers so that they can make sense of what is being communicated. This approach, although described as outdated by some, is useful especially for higher education students who are studying this genre for the first time. The texts included in the analysis are China Mieville’s novel Perdido Street Station, Ted Chiang’s novella “Liking What You See: A Documentary” as well as two short stories - Mike Resnick’s “The Elephants on Neptune” and Michael Swanwick’s “The Dead”.